Responsive Elections: Political Campaign in 2024 Local Election - Fatmawati Moekahar; Norhayati Rafida; Fitri Hardianti; Elfa Sabilal Hikmah (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
This study aims to analyze public responses to political campaign messages delivered by candidates in the 2024 Riau Local Election. In this local political contest, each candidate highlights issues, narratives, and cultural symbols that reflect regional identity, with the aim of building emotional closeness with the voting public. This study used a qualitative approach by exploring public opinion on political campaign messages disseminated through social media, billboards, and local mass media. The results show that public responses to campaign messages in the 2024 Riau local election tend to align with cultural values, particularly those of Riau Malay culture. The visions, missions, programs, slogans, and campaign activities of all candidates contain symbols of Riau Malay culture. The political messages contained in this political campaign are considered part of an effort to preserve Riau Malay culture, although often not accompanied by concrete policy plans especially regarding crucial issues in Riau. The approach to Riau Malay cultural values in a symbolic form can increase emotional resonance and moral legitimacy. These findings indicate that the resonance of political messages with local culture is a key factor in shaping public perception and support in the 2024 Riau local election. This research contributes to the study of local political communication by showing how the meaning and acceptance of campaign messages are determined by the regional socio-cultural context.